Uprooting, removing and relocating populations: The role and significance of internal displacement in the syrian regime’s integrated military–political war strategy - Samer Bakkour; Rama Sahtout (Comparative Migration Studies)
Abstract International actors have only relatively recently recognized that internal displacement is a strategy, as well as a consequence, of violent conflict, and the subject accordingly continues to give rise to a host of misinterpretations and misunderstandings, including the tendency to view it as a protection challenge, which persists despite the fact that state actors, as the supposed protectors, are also invariably the main perpetrators of displacement. This article seeks to explore and establish the ‘place’ of internal displacement in the Syrian Regime’s political and military strategy in Assad’s ongoing war on the Syrian people. It draws on an emerging literature on displacement, along with a range of reports on the Regime’s internal displacement activities in the Civil War, to propose that it needs to be engaged and understood as a rational strategy that is being applied to alter existing demographic realities. After zooming in to focus on strategic displacement in particular, it seeks to demonstrate that displacement should not just be understood in terms of its military significance, but also as a mechanism that the Regime uses to reconfigure and rearrange existing political and social realities.